POLRESTA JAKABARING PERFORMANCE in the SERVICE of MANUFACTURING Drive Licence (SIM) in PALEMBANG - SAPUTRA, SUEB; Rares, Joyce Jacinta; Lengkong, Florence Daicy (Sam Ratulangi University, 2016)
ABSTRACT: public service is the process of simultaneously output showing how government functions running. The implementation of decentralization and regional autonomy in Indonesia is believed to be able to improve services to the community, improve people's welfare, and fostering democracy. Effected by the importance of the role of public services on the one hand and the number of issues that bind them on the other hand, issues concerning the performance of the institutions as well as public service apparatus became one of the important issues in the reform of public administration in different countries, including for the context of contemporary Indonesia. Driving licences (SIM) is one of the mandatory documents which must be owned by citizens of Indonesia who drive good or rodadua. In addition to a license for motorists, driving licences can also be used as proof of identity for its owners in various other administrative affairs, thus maintaining a driver's licence (SIM) become important in order not to hamper travel and other affairs. POLRESTA Jakabaring Palembang was a place where the public can obtain a driver's license (DRIVING LICENCE) with the hope of driving licences (SIM) they can be retrieved quickly, easily and inexpensivelyRESEARCH METHODOLOGY: this study uses Qualitative research methods, descriptive through in-depth interviews to 8 Informant, observation, search and document additional instruments be assisted with guidelines for interviewing, recording device, and stationery to write. RESEARCH RESULTS: based on indicators of Dwiyanto used in this penerlitian, productivity, service quality, Responsiveness, Accountability and corporate responsibility, then note that the performance of POLRESTA Jakabaring in the service of Creation Licence (SIM) is already quite good even though there are still some things that need to be improved such as the responsiveness of the officer service in the future. Conclusion: the performance of POLRESTA Jakabaring Palembang is based on research conducted in the offices of POLRESTA Jakabaring has been running pretty well, but still requires improvement.Keyword: Performance POLRESTA Jakabaring, servicing the manufacturing Licence (SIM)